A Study of the Acceptance and Accommodation of Calvinism in the Korean Presbyterian Church - Seong, ShinHyung (International review of mission, 2018)
This research delves into the acceptance and accommodation of Calvinism in the Korean Presbyterian Church, concentrating on the Pyungyang Mission Station of Chosun-ya-so-kyo (Korean Presbyterian Church) in the 1900s to 1930s. It has been suggested that Chosun-ya-so-kyo did not fully introduce Calvinism during this early period of Korean mission because of its historical and cultural limitations. Based on materials such as church history textbooks and academic journals, however, this study argues that Chosun-ya-so-kyo clearly accommodated Calvinism as its theological foundation. In particular, the mission station's theology education institution developed theological analysis of Calvinism through three perspectives: forging missionaries, Korean conservative theologians, and liberal theologians. Thus, the Korean Presbyterian Church adopted Calvinism as its theological groundwork.